Structural characterization of highly glucosylated crocins and regulation of their biosynthesis during flower development in Crocus - AHRAZEM, OUSSAMA; Rubio Moraga, Angela; JIMENO, MARIA LUISA; Gómez-Gómez, Lourdes (Frontiers in Plant Science, 2015)
Crocin biosynthesis in Crocus has been proposed to proceed through a zeaxanthin cleavage pathway catalyzed by carotenoid cleavage dioxygenase 2 (CCD2), and followed by glucosylation reactions catalyzed by CsGT2 (UGT74AD1). In Crocus ancyrensis flowers, crocins with eight (crocin-1), seven (crocin-2) and six glucose (crocin-3) moieties accumulated both in stigma and tepals. We have characterized the structure of these highly glucosylated crocins and follow up their accumulation by high-resolution liquid chromatography coupled with diode array detector along the development of both tissues, and coupled to the isolation and analysis of the expression of eighteen genes (PSY-I, PSY-II, PDS-(I-V), ISO-ZDS, ZDS, CtrISO, LYC-I and II, BCH, CaCCD2, UGT74AD2-5) related with the apocarotenoid metabolism in C. ancyrensis tepals and stigmas. Structure elucidation of crocin-1 and crocin-2 was done by the combined use of 1D and 2D [1H, 1H] (gCOSY and TOCSY and ROESY) and [1H-13C] NMR experiments, revealing that for crocin-1 was all-trans-crocetin O-[β-D-Glucopyranosyl)-(1→4)-(β-D-glucopyranosyl)-(1→2)]-O-[β-D-glucopyranosyl-(1→6)]-β-D-glucopyranosyl diester, while crocin-2 showed an identical structure except for the absence of one glucose residue in one end of the molecule. Crocins accumulation was not synchronically regulated in stigma and tepals, although in both cases crocins accumulation parallels tissue development, decreasing at anthesis. The expression of the carotenogenic genes PSY, ZDS-V, BCH and LCY-II was correlated with crocins accumulation. In addition, CaCCD2 and only one of the four glucosyltransferase encoding genes, UGT74AD2, were highly expressed, and the expression was correlated with high levels of crocins accumulation in stigma and tepals.